Pemberdayaan Masyarakat Dalam Pemanfaatan Limbah Kulit Salak Menjadi Produk Unggul Melalui Model Industri Kreatif Di Kecamatan Kapas Kabupaten Bojonegoro - Abdul Ghofur; Yuhronur Efendi; Mohammad Rizal Nur Irawan (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2020)
Home industry "Mother Arum" is a home industry in the area of ​​Bojonegoro salak wedi agrotourism and produces a variety of preparations from salak fruit such as date palm, madumongso salak, dodol salak, molen salak, and coffee zalacca seeds. Organic waste in the form of zalacca skin which is the residual consumption of zalacca or the rest of zalacca processing for other food products that are currently produced in this home industry and the local community is very abundant. Phytochemical test results showed the skin of zalacca contains flavonoids and tannins and a little alkaloid. The content of flavonoids in zalacca skin extract can reduce glucose levels in the blood. The ethanol extract of zalacca skin contains secondary metabolites of alkaloids, polyphenolates, flavonoids, 1mbien, quinones, monoterpenes and sesquiterpenes. Based on the value of antioxidant capacity and IC50, zalacca skin extract has great potential to be marketed as a food product as an antioxidant drink that is good for health, but also as an effort to use zalacca skin so that it has economic value. The solution to this problem is to process wedi zalacca skin into a processed product in the form of zalacca tea and make its marketing strategy online or offline. The proposed activity plan is the training of salak skin production in the "Mother of Arum" home industry and the creation of a marketing strategy. This is expected to be able to provide knowledge, skills and increase competitiveness in the form of product diversification in the "Mother of Arum" home industry. Keywords: Productivity, Machinery, Electric Motors, Production Capacity